Porous MOF‐205 with multiple modifications for efficiently storing hydrogen and methane as well as separating carbon dioxide from hydrogen and methane. (15th July 2019) - Xu, Genjian; Meng, Zhaoshun; Liu, Yuzhen; Guo, Xiaojian; Deng, Kaiming; Ding, Lifeng; Lu, Ruifeng
Summary: In this work, quantum mechanical calculations and grand canonical Monte Carlo simulations were performed to study H2 and CH4 uptakes as well as CO2 separation from CH4 or H2 in MOF‐205 with different modification approaches. Upon C48 B12 impregnation and Li decoration, B‐doped MOF‐205 shows remarkably improved gas adsorption and separation performances. Under ambient condition, both H2 and CH4 storage capacities in the modified materials meet the targets set by the US Department of Energy. Moreover, Li doping greatly increases the separation selectivity of CO2 in CO2 /CH4 and CO2 /H2 mixtures. This multiple modifications strategy opens the door to the production of porous nanomaterials with higher gaseous adsorption and separation capabilities. Abstract : The gas adsorption and separation performances in C48 B12 ‐impregnated, Li‐decorated, and B‐doped MOF‐205 are explored via multiscale theoretical simulations. Both H2 and CH4 storage capacities in the modified MOF‐205 meet the targets set by the US Department of Energy. The separation selectivity of CO2 in CO2 /CH4 and CO2 /H2 mixtures are greatly improved in the modified MOF‐205.